De Bosra à Palmyre, l’archéologie face au chaos - Pierre-Marie Blanc (Les Cahiers d’EMAM)
Two main cities from antique Syria, as Palmyra and Bosra (Bostra), classified in the Unesco World Heritage list, have, within the syrian war since 2011, tragical but different destinity. The archaeological perception of the town of Bosra, slowly reveled by national and international teams from the end of the 60’s, was considerably enriched during the first decade of the 21th century, before to be stopped by war. Resilience of inhabitants, workers of their own history, is aknowledged by an archaeologist, who spend a large part of his carrieer studying material culture and architecture who have facionnating the city since eight millennium.